Making Babies in Early Modern England - Astbury, Leah (Cambridge University Press, 2026)
Early modern English people were obsessed with making babies. Leah Astbury traces this preoccupation through manuscript letters, diaries, recipe books and almanacs, revealing its centrality to the histories of gender, medicine, social status, as well as family life. This title is also available as open access on Cambridge Core.